Coffee to Go! Modeling Thermoclines in Multivariable Calculus. Issue 1 (2nd January 2020) - Bruder, Andrea; Kohler, Brynja R.
Abstract: Although modeling is an integral process in applied mathematics, students rarely encounter modeling opportunities in their calculus courses. We introduce a laboratory experience as a starting point for calculus students to investigate multivariable functions. A layered system of coffee and milk serves as a physical model for temperature gradients in lakes or the atmosphere, where temperature depends on temporal and spatial variables. Students collect temperature data, graph the data, develop mathematical models to fit the data, and write a report about their findings. This article includes details about the class activity conducted in two different college settings and provides our assessment of student learning and interaction with the lab.